MEMS-based passive wireless respiration profile sensor - Moradian, Sina; Abdolvand, Reza (IEEE SENSORS 2016 : Orlando, Florida, USA, October 30-November 2, 2016 : 2016 proceedings papers, 2016)
In this paper we present a sensor that wirelessly records the breathing profile of the human respiratory system. The sensor works passively and does not contain a power source. Furthermore, it is lightweight, robust and flexible making it ideal as a wearable monitoring device. The sensor is made of a ~902MHz thin film piezoelectric-on-substrate (TPoS) MEMS resonator and an ultra-high frequency (UHF) antenna made of a thin metal film formed on a flexible substrate. The resonance frequency of the TPoS resonator shifts in response to the inhaled/exhaled air flow and a wireless detection technique is utilized to sense the frequency shift and to translate it into the respiration profile. The Respiration profile of a subject is measured and presented for a sensor-to-transceiver distance of ~25cm.